Dermal Spray Formulation of Meloxicam - Singh Kang, Sagar; Jyoti, Kiran (International Journal of Psychosocial Rehabilitation, 2019)
Pain and inflammation, often seen in the form of “edema” (swelling) is one of the most common conditions which affect the animals due to injuries. Inflammation is a localised protective response stimulated by injury or destruction of tissues, which serves to dilute, destroy or wall off both the injurious agent and the injured tissue. The classic signs of inflammation are heat, redness, pain, swelling and loss of function. Numerous numbers of treatments via oral and parenteral route of administration are available for treating the conditions of pain and inflammation in animals. Though meloxicam demonstrated good oral bioavailability (76%) in cattles; however; oral and parenteral administration of meloxicam are associated with GI distress, vomiting, soft stools, diarrhea, in appetence and suboptimal concentration at the site of inflammation. NSAIDs skin delivery offers a number of benefits over the oral route associated with potential side effects. Therefore, the aim of this study is to provide a dermal spray formulation of a meglumine salt of meloxicam for the treatment of pain and inflammation in cattles. Meloxicam spray was then estimated with respect to different physicochemical parameters such as pH, drug content and Homogeneity.